Analisis Yuridis Terhadap Keabsahan Perjanjian Investasi Dalam Transaksi Initial Coin Offering (ICO) Berdasarkan Pasal 1320 Kitab Undang-Undang Hukum Perdata: Juridical Analysis of Validity of Investment Agreement in Initial Coin Offering (ICO) according to Article 1320 of Civil Law - Hashifah, Adinda Salwa; Sulistyarini, Rachmi; Ganindha, Ranitya (Warkat, 2023)
Initial coin offering (henceforth referred to as ICO) as one of the investment developments in the digital era has left legal loopholes over the execution of the ICO in Indonesia, coupled with the emergence of cryptocurrency. This research aims to analyze the validity of an investment agreement on the ICO using cryptocurrency as a payment method along with its legal consequences. With normative-juridical methods, the research results have found out the agreement of the ICO is deemed unlawful according to Article 1320 of the Civil Code due to the clause contravening the legislation, leading to the failure of the fulfillment of the halal clause. Thus, the agreement is deemed to be void ab initio or simply inexistent. Due to the absence of the regulatory provision regulating the ICO, the investors involved could file a lawsuit over the violation harming the parties running the ICO. Thus, it is important to formulate regulatory provisions concerning the ICO in Indonesia that set forth the measures taken to provide legal protection for the aggrieved inventors due to the void ab initio agreement. These regulatory provisions are expected to avert any ICO-related problems as stated above.